Isolation of Microvascular Endothelial Tubes from Mouse Resistance Arteries - Socha, Matthew J. (MyJove Corporation, 2013)
The control of blood flow by the resistance vasculature regulates the supply of oxygen and nutrients concomitant with the removal of metabolic by-products, as exemplified by exercising skeletal muscle. Endothelial cells (ECs) line the intima of all resistance vessels and serve a key role in controlling diameter (e.g. endothelium-dependent vasodilation) and, thereby, the magnitude and distribution of tissue blood flow. The regulation of vascular resistance by ECs is effected by intracellular Ca(2+) signaling, which leads to production of diffusible autacoids (e.g. nitric oxide and arachidonic acid metabolites)(1-3) and hyperpolarization(4,5) that elicit smooth muscle cell relaxation. Thus understanding the dynamics of endothelial Ca(2+) signaling is a key step towards understanding mechanisms governing blood flow control. Isolating endothelial tubes eliminates confounding variables associated with blood in the vessel lumen and with surrounding smooth muscle cells and perivascular nerves, which otherwise influence EC structure and function. Here we present the isolation of endothelial tubes from the superior epigastric artery (SEA) using a protocol optimized for this vessel. To isolate endothelial tubes from an anesthetized mouse, the SEA is ligated in situ to maintain blood within the vessel lumen (to facilitate visualizing it during dissection), and the entire sheet of abdominal muscle is excised. The SEA is dissected free from surrounding skeletal muscle fibers and connective tissue, blood is flushed from the lumen, and mild enzymatic digestion is performed to enable removal of adventitia, nerves and smooth muscle cells using gentle trituration. These freshly-isolated preparations of intact endothelium retain their native morphology, with individual ECs remaining functionally coupled to one another, able to transfer chemical and electrical signals intercellularly through gap junctions(6,7). In addition to providing new insight into calcium signaling and membrane biophysics, these preparations enable molecular studies of gene expression and protein localization within native microvascular endothelium.